The Concept of the Collection "Ekphrasis in Russian Literature": On the Question of the Theoretical Characteristics of the Term - Ю. Г. Цой (Scientific Trends, 2024)
Within the framework of this article, an attempt is made to characterize the concept of "pictorial ekphrasis", as well as the concept of one of the most significant publications in this field – the collection of the Lausanne Symposium. The category of "ekphrasis" is at the center of many modern hermeneutic studies and significantly enriches the perception of works of art.
Keywords: Ekphrasis, pictorial ekphrasis, art, text, writer, reader.